Quest and achievements: on the 60th birth anniversary and 20 years of directorship of Vasyl Fedorovych Chekhun (Experimental Oncology, 2016)
In November 2016 Director of R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of the NAS of Ukraine, Editor-in-Chief of “Experimental Oncology” Academician of the NAS of Ukraine Vasyl Chekhun celebrated his 60th birth anniversary.